Regional Emergency Stroke Quick-Response (RESQ) Network: a proposed paradigm of Malaysia stroke care services - Chia, Peck Kee; Mohamad, Nur Afiqah; Inche Mat, Liyana Najwa; Itam @ Ismail, Iskasymar; Yusof Khan, Abdul Hanif Khan; Loh, Wei Chao; Wan Sulaiman, Wan Aliaa; Hoo, Fan Kee; Abdul Rahim, Ezamin; Muda, Ahmad Sobri; Basri, Hamidon (Faculty of Medicine and Health Science, Universiti Putra Malaysia, 2020)
Stroke care service in Malaysia is suboptimal despite the fact that it is one of the commonest cause of death. This is due to several limitations, including lack of resources and funding for the stroke care establishment and the management itself. Alternatively, other regions have come up with numerous ways to combat the difficulties in order to provide better stroke care services. We have identified the overwhelming benefits of creating stroke care units, thrombolysis services, and endovascular thrombectomy. For this reason, we designed a Regional Emergency Stroke Quick Response Network (RESQ) based on the needs of the current situation in Malaysia. With a standardised RESQ training, we hope to achieve close-knitted cooperation in between the emergency medical services, emergency department team and the RESQ, which subsequently will create an ideal improvised stroke care units.